Florida's Property Tax Reform: Implications for Your Tax Bill from Proposed Constitutional Changes - Rodney L. Clouser (EDIS)
FE706, a 5-page fact sheet by Rodney L. Clouser, is part of the Florida’s Property Tax Reform series. It provides an overview of the proposed constitutional amendment, and explains how each proposed change works, discussing scenarios for each. Includes references. Published by the UF Department of Food and Resource Economics, December 2007.